Effects and dose-response relationship of balance training on balance performance in youth: A systematic review and meta-analysis - Gebel, A.; Lesinski, M.; Behm, D. G.; Granacher, U. (Sports Medicine, 2018)
This systematic review and meta-analysis quantified the effects and dose-response relationships following balance training (BT) in youth. We found that BT is an effective means to improve balance irrespective of age, sex, training status, setting and testing method.